"The qualitative method is more humane": Perspectives generated from the application of a focus group in accounting sciences - Melo, Victoria Puntriano Zuniga de; Fideles, Thales Ferreira; Jó, Águeda Teotônio; Tavares, Lyandra Simplício (Seven Editora, 2024)
The aim of this article is to analyze the contributions of the focus group collection method applied in the subject "Qualitative Methods for Research in Accounting" at a Higher Education Institution (HEI) with the aim of gathering students perspectives on their experiences as Accounting undergraduates who are often presented with the quantitative research method. The methodology used was qualitative, applied in nature, using an exploratory approach to support the focus groups and the analysis of the results obtained, as well as bibliographical and multi-case procedures. The data was collected through two focus groups: one face-to-face and one online, followed by reports. Thus, among the results of the application of the Focus Group, it was observed the opening of new horizons in the field of academic research for students in the discipline and the rare use of qualitative methods in Accounting Sciences. DOI:https://doi.org/10.56238/sevened2024.007-075